Multivesicular Bodies Mature from the Trans-Golgi Network/Early Endosome in Arabidopsis([W]) - Scheuring, David (American Society of Plant Biologists, 2011)
The plant trans-Golgi network/early endosome (TGN/EE) is a major hub for secretory and endocytic trafficking with complex molecular mechanisms controlling sorting and transport of cargo. Vacuolar transport from the TGN/EE to multivesicular bodies/late endosomes (MVBs/LEs) is assumed to occur via clathrin-coated vesicles, although direct proof for their participation is missing. Here, we present evidence that post-TGN transport toward lytic vacuoles occurs independently of clathrin and that MVBs/LEs are derived from the TGN/EE through maturation. We show that the V-ATPase inhibitor concanamycin A significantly reduces the number of MVBs and causes TGN and MVB markers to colocalize in Arabidopsis thaliana roots. Ultrastructural analysis reveals the formation of MVBs from the TGN/EE and their fusion with the vacuole. The localization of the ESCRT components VPS28, VPS22, and VPS2 at the TGN/EE and MVBs/LEs indicates that the formation of intraluminal vesicles starts already at the TGN/EE. Accordingly, a dominant-negative mutant of VPS2 causes TGN and MVB markers to colocalize and blocks vacuolar transport. RNA interference–mediated knockdown of the annexin ANNAT3 also yields the same phenotype. Together, these data indicate that MVBs originate from the TGN/EE in a process that requires the action of ESCRT for the formation of intraluminal vesicles and annexins for the final step of releasing MVBs as a transport carrier to the vacuole.